Analysing teacher’s feedback used by an English teacher of EFL in senior high school - Dwi Nur Oktaviani (Politeknik Negeri Bali, 2020)
This research reports an analysis of giving feedback from the teacher to the students after showing their speaking performance in the classroom. Data were collected from a teacher and six students through interviews and documentation. These six students are chosen from the high, medium, and low level based on their score and their performance in the class. Data analysis discovered that the teacher concern with giving explicit, clarification requests, elicitation, and repetition feedback. In giving feedback the teacher focused to correct how they pronounce the words and how they arrange the sentence grammatically. In addition, giving online feedback has several benefits for both the teacher and the learner. For the teacher giving feedback can tell the teacher how about students' minds. Knowing the students' minds will help the teacher to choose the style in teaching. Then for the students, getting feedback also give them many benefits. These are: Students can communicate more with the teacher, students will be more confident, students will be more motivated to speak English, a student can realize their mistake, students can revise the mistake, a student can decrease their mistakes, then a student can develop their speaking.